Analisis Peletakan dan Kebutuhan Proteksi Katodik Pada Mooring Buoy di Pertamina Fuel Terminal Luwuk - Windi Widianingrum; Juswan Sade; Habibi Palippui (Departemen Teknik Kelautan Universitas Hasanuddin, 2021)
Corrosion is one of the most common causes of damage to mooring buoys due to oxidation on the surface of the steel plate. The purpose of this study was to determine the need and placement of cathodic protection as well as the costs involved in providing cathodic protection for mooring buoys using the rules of BKI (Indonesian Classification Bureau) and DNV (Det Norske Veritas Industry Norway). In the cathodic protection system, there are two methods of cathodic protection, namely Sacrificial Anode Cathodic Protection (SACP) and Impressed Current Cathodic Protection (ICCP). In this study, the Sacrificial Anode method was used because the installation is simpler so that it does not require special skills and the anode connector is cathodically protected. Mooring buoy 2.380 meters high, 3.200 meters in diameter with a cathodic protection design life of 5 years. The anode used in this study was a Longated flush-mounted Z9.0H1 (Welded Type) anode with dimensions of 355 x 85 x 45 mm. From the results of this study, the total anode mass needed to protect the mooring buoy is 48 kg with the distance between the anodes on the topside hull plate is 2.000 m and the hull bottom swim plate is 3.000 m and the estimated cost required in providing mooring buoy cathodic protection is Rp. 7,487,075.